Entrepreneurial Change in Social Responsibility - Ahmad AlFahad; Majdi Anwar Quttainah (AIBPM Publisher, 2018)
It is well known that social responsibility is a major driver of a firm’s image, it could take it south if the term “social responsibility” is totally neglected by the firm. Overwhelming in that term could also have a negative side effect specially if the thing the firm contributing in wasn’t something tangible to a specific segment of the community with demographics of pride and dignity. Upon our extended abstract, we demonstrated our project that we intend to implement a variety of departments that each has a task to perform.